Efficacy and safety of intravitreal injection of conbercept for moderate to severe nonproliferative diabetic retinopathy - Shen, Lu; Zheng, Yuxiang; Gao, Zelan; Li, Qirui; Dai, Min; Yang, Wenchang; Zhang, Qiying; Li, Dongli; Hu, Yijun; Yuan, Ling (Frontiers in Medicine, 2024)
Purpose This study aimed to assess the effectiveness and safety of intravitreal injection of conbercept (IVC) in treating moderate to severe nonproliferative diabetic retinopathy (NPDR), with or without accompanying diabetic macular edema. Methods In this longitudinal retrospective study, 35 patients (50 eyes) with moderate to severe NPDR and Diabetic Retinopathy Severity Scale (DRSS) scores between 43 and 53 were treated at the Department of Ophthalmology, First Affiliated Hospital of Kunming Medical University, from October 2018 to January 2023. Treatment protocol included three monthly IVC injections followed by a pro re nata (PRN) regimen over a two-year follow-up period. Outcome measures were best-corrected visual acuity (BCVA), intraocular pressure, central macular thickness (CMT), extent of hard exudate (HE), and changes in DRSS scores. DRSS scores before and after treatment were analyzed using the Wilcoxon rank-sum test. Both systemic and ocular adverse events were meticulously documented to ascertain safety. Results From baseline to the final follow-up, the mean BCVA improved from 0.41 ± 0.39 to 0.23 ± 0.20 logMAR (p<0.05). The mean CMT decreased from 306.22 ± 77.40 to 297.97 ± 88.15 μm (p = 0.385). At 24 months, DRSS scores improved by ≥1 stage in 40 eyes (80%), ≥ 2 stages in 28 eyes (56%), ≥3 stages in 10 eyes (20%), and remained stable in 6 eyes (12%). The DRSS scores at each follow-up interval demonstrated statistically significant improvement from baseline (p<0.05). In 15 of 27 eyes (55.56%) with diabetic macular edema (DME), there was a significant reduction in the mean area of HE from baseline (p<0.05). No serious systemic adverse events were observed. Conclusion IVC is an effective and safe treatment for moderate to severe NPDR, demonstrating significant improvements in DRSS scores.